Systemic sclerosis (Scleroderma) Among Adults Attending the Rheumatology Clinic of a Tertiary Institution - Oguntona SA; Olatunde OA; Bakare BO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: Systemic sclerosis is a multi-systemic autoimmune disorder characterised by the generation of autoantibodies, massive deposition of collagen and other matrix substances in the connective tissues and alterations of the microvasculature. Methods: This was a prospective study of all the cases of scleroderma seen between January 2012 and June 2015 at the Rheumatology Clinic of the Olabisi Onabanjo University Teaching Hospital. All the patients with the diagnosis of scleroderma were included. Excluded from the study were patients with other skin lesions not typical of scleroderma. Results: Six hundred and six patients with rheumatologic disorders were seen over the study period but eight of them had scleroderma. All the eight cases of scleroderma were females. The age range was 36-52 years with a mean age of 45 years (SD ± 11.4 years). All the cases had arthritis and diffuse skin lesions. Other features included sclerodactyly, microstomia and salt and pepper skin appearance in all the eight cases while Raynaud's phenomenon and leg ulcers were not frequent. Inflammatory marker (erythrocyte sedimentation rate) was significantly elevated in all the cases. Renal and cardiovascular complications were the leading causes of death. Conclusion: Diffuse systemic sclerosis is a more serious disease than the limited form. Early referral of patients with skin lesions suggestive of scleroderma to a specialist centre is recommended as symptomatic treatment helps to improve the quality of life.